2019
DOI: 10.2174/1385272823666190723141347
|View full text |Cite
|
Sign up to set email alerts
|

Review of Progress in Predicting Protein Methylation Sites

Abstract: Protein methylation is an important and reversible post-translational modification that regulates many biological processes in cells. It occurs mainly on lysine and arginine residues and involves many important biological processes, including transcriptional activity, signal transduction, and the regulation of gene expression. Protein methylation and its regulatory enzymes are related to a variety of human diseases, so improved identification of methylation sites is useful for designing drugs for a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…This has meant that the stable and critical epigenetic modification style, methylation, has become most viable candidate for colon cancer biomarker research (Cheng et al, 2018;Hong, 2018;Tang et al, 2018;Wang et al, 2019). The abnormal DNA methylation pattern associated with colon cancer has been verified (Simmer et al, 2012;Ao et al, 2019;Zuo et al, 2020). High and low methylated CpG sites have been identified using the data of Illumina Human Methylation 450K (Naumov et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This has meant that the stable and critical epigenetic modification style, methylation, has become most viable candidate for colon cancer biomarker research (Cheng et al, 2018;Hong, 2018;Tang et al, 2018;Wang et al, 2019). The abnormal DNA methylation pattern associated with colon cancer has been verified (Simmer et al, 2012;Ao et al, 2019;Zuo et al, 2020). High and low methylated CpG sites have been identified using the data of Illumina Human Methylation 450K (Naumov et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation regulates temporal and spatial gene expression and condition-dependent phenotypic traits, including changing flower symmetry [ 9 ] or phenotypic plasticity [ 10 ] in different biological processes [ 11 ]. Histone methylation, as a vital and reversible post-translational modification (PTM), is one of the most important modifications on histone lysine (K) and arginine (R) residues and regulates many crucial biological processes [ 12 ]. RNA methylation is an important modification in plant development and the abiotic stress response.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that 5hmC, 6mA, and 4mC, and others are widely present in the genome, and significant progress has been made ( Wu et al, 2016 ; Ao et al, 2019 ; Hu et al, 2019 ; Zhu et al, 2019 ; Zou et al, 2019 ; Cai et al, 2020 ; Fu et al, 2020 ; Hong et al, 2020 ). However, methylation-related technologies-the short-read sequencing and long-read have major disadvantages.…”
Section: Introductionmentioning
confidence: 99%